2009
DOI: 10.1182/blood-2008-05-160747
|View full text |Cite
|
Sign up to set email alerts
|

Complete eradication of human B-cell lymphoma xenografts using rituximab in combination with the immunocytokine L19-IL2

Abstract: The antibody-mediated delivery of therapeutic agents to sites of angiogenesis is an attractive strategy for anticancer therapy, but is largely unexplored in hematologic malignancies. In the present study, we show that the extra domain B (EDB) of fibronectin, a marker of angiogenesis, is expressed in B-cell non-Hodgkin lymphoma (NHL) and that the human monoclonal anti-EDB antibody L19 can selectively localize to the lymphoma-associated subendothelial extracellular matrix. In vivo, the preferential accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 45 publications
5
122
0
Order By: Relevance
“…12,39,40 As for the previous two models, a quantitative biodistribution study and an ex vivo immunofluorescence analysis following intravenous administration confirmed a preferential accumulation of F8-IL4 around tumor neovascular structures (Figs. 6a and 6b).…”
Section: In Vivo Studies In A20 Tumor-bearing Micementioning
confidence: 92%
“…12,39,40 As for the previous two models, a quantitative biodistribution study and an ex vivo immunofluorescence analysis following intravenous administration confirmed a preferential accumulation of F8-IL4 around tumor neovascular structures (Figs. 6a and 6b).…”
Section: In Vivo Studies In A20 Tumor-bearing Micementioning
confidence: 92%
“…An immunocytokine fusion protein combining IL2 with an antifibronectin antibody in combination with rituximab was found to eradicate B-cell lymphoma xenografts (32). Antibodies directed against the inhibitory Kir molecules expressed by NK cells have been evaluated in combination with rituximab (33).…”
Section: Discussionmentioning
confidence: 99%
“…The alternatively spliced domains extra domain A (EDA) and extra domain B (EDB) of fibronectin, which are targeted by the F8 and L19 antibodies, respectively, exhibit a high level of conservation among species and are virtually undetectable in normal tissues; however, they are abundantly expressed in the stroma and neovasculature of most aggressive types of human cancers 96,[102][103][104][105][106][107][108][109][110] . Similarly, systematic chemical proteomics studies 107,[111][112][113] have recently shown that another component of the extracellular matrix, periostin, exists in several splice isoforms that are abundantly found in most types of cancers [111][112][113][114] .…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%